2010
DOI: 10.1016/j.cub.2010.03.057
|View full text |Cite|
|
Sign up to set email alerts
|

An S-Acylation Switch of Conserved G Domain Cysteines Is Required for Polarity Signaling by ROP GTPases

Abstract: Rho GTPases are master regulators of cell polarity. For their function, Rhos must associate with discrete plasma membrane domains. Rho of Plants (ROPs) or RACs comprise a single family. Prenylation and S-acylation of hypervariable domain cysteines of Ras and Rho GTPases are required for their function; however, lipid modifications in the G domain have never been reported. Reversible S-acylation involves the attachment of palmitate (C16:0) or other saturated lipids to cysteines through a thioester linkage and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 30 publications
4
79
0
Order By: Relevance
“…This could be because ROP10CA and ROP10DN are possibly localized at different membrane microdomains in the PM. In fact, GTP-bound type I ROP6 of Arabidopsis is partitioned exclusively to lipid rafts by S-acylation to stabilize the protein's interaction with the PM (Sorek et al, 2007(Sorek et al, , 2010. Similarly, the activated type II ROP11 (RAC10) of Arabidopsis, one of the closest homologs of ROP10, was detected in lipid rafts (Bloch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This could be because ROP10CA and ROP10DN are possibly localized at different membrane microdomains in the PM. In fact, GTP-bound type I ROP6 of Arabidopsis is partitioned exclusively to lipid rafts by S-acylation to stabilize the protein's interaction with the PM (Sorek et al, 2007(Sorek et al, , 2010. Similarly, the activated type II ROP11 (RAC10) of Arabidopsis, one of the closest homologs of ROP10, was detected in lipid rafts (Bloch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoylation plays a key role in targeting proteins to PM microdomains (Levental et al, 2010). Arabidopsis ROP6, a type I ROP possessing a CaaL box motif, is primarily geranylgeranylated and, when activated, accumulates in DRMs with transient palmitoylation (Sorek et al, 2007(Sorek et al, , 2010. In addition, mammalian Rac1 is palmitoylated at C178, a modification that is essential for targeting to rafts and actin cytoskeleton remodeling (NavarroLérida et al, 2012), and present in not only rafts but also non-rafts, where Rac1 is predominantly inactivated (Moissoglu et al, 2014).…”
Section: Role Of Pm Microdomains In the Rac1-rbohb/h-mediated Mti Patmentioning
confidence: 99%
“…Under physiological conditions, the interaction between RhoGDI and the RHO family of proteins was shown to depend on geranylgeranylation of the GTPase (Hoffman et al, 2000;Grizot et al, 2001;Garcia-Mata et al, 2011). Since recombinant ROPs expressed in E. coli are not geranylgeranylated (Sorek et al, 2010), it was important to establish that RhoGDI1 interacts with geranylgeranylated ROP2 purified from plants. To this end, we prepared protein extracts from GFP-ROP2 seedlings and examined whether GFP-ROP2 could be pulled down by GST-AtRhoGDI1/SCN1.…”
Section: Rop2 Activation By Map18 Is Independent Of Microtubules or Amentioning
confidence: 99%
“…Previous studies have shown that several ROPs can affect root hair growth (Molendijk et al, 2001;Jones et al, 2002;Bloch et al, 2005;Sorek et al, 2010). ROP2, ROP4, and ROP6 were shown to accumulate at the root hair initiation site (Molendijk et al, 2001;Jones et al, 2002;Payne and Grierson, 2009).…”
mentioning
confidence: 94%
See 1 more Smart Citation